SUSTAINABLE NITROGEN AND CARBON CYCLING IN AFGHANISTAN AGROECOSYSTEMS: CHALLENGES AND OPPORTUNITIES - Nazir Khan Mohammadi*; Gul Arabzai Mohammad**; Wang Zikui*** (Natural Resources and Sustainable Development, 2025)
Nitrogen and carbon cycling are essential for soil fertility, crop productivity, and environmental sustainability in agroecosystems. In Afghanistan, where agriculture is vital for food security and economic stability, a thorough understanding of these cycles is crucial for developing sustainable farming practices. This study investigates nitrogen and carbon transformation processes, including fixation, mineralization, nitrification, and denitrification, emphasizing their impacts on soil health and nutrient availability. It underscores the importance of integrating traditional and modern agricultural techniques, such as crop rotation, intercropping, biochar application, and organic amendments, to enhance use efficiency and decrease reliance on synthetic fertilizers. Additionally, this research evaluates various cropping systems—monocropping, intercropping, and legume-based nutrient rotations—regarding their effects on nitrogen retention, carbon sequestration, and overall soil health. While traditional water management practices, such as karezes and Mir Ab systems, promote sustainable agriculture, modern intensive farming can lead to challenges like soil degradation and